Development of biodegradable bioactive glass ceramics by DLP printed containing EPCs/BMSCs for bone tissue engineering of rabbit mandible defects. (March 2020) - Xu, Fangfang; Ren, Hui; Zheng, Mengjie; Shao, Xiaoxi; Dai, Taiqiang; Wu, Yanlong; Tian, Lei; Liu, Yu; Liu, Bin; Gunster, Jens; Liu, Yaxiong; Liu, Yanpu
Abstract: Bioactive glass ceramics have excellent biocompatibility and osteoconductivity; and can form direct chemical bonds with human bones; thus, these ceramic are considered as "Smart" materials. In this study, we develop a new type of bioactive glass ceramic (AP40mod) as a scaffold containing Endothelial progenitor cells (EPCs) and Mesenchymal stem cells (BMSCs) to repair critical-sized bone defects in rabbit mandibles. For in vitro experiments: AP40mod was prepared by Dgital light processing (DLP) system and the optimal ratio of EPCs/BMSCs was screened by analyzing cell proliferation and ALP activity, as well as the influence of genes related to osteogenesis and angiogenesis by direct inoculation into scaffolds. The scaffold showed suitable mechanical properties, with a Bending strength 52.7 MPa and a good biological activity. Additionally, when EPCs/BMSCs ratio were combined at a ratio of 2:1 with AP40mod, the ALP activity, osteogenesis and angiogenesis were significantly increased. For in vivo experiments: application of AP40mod/EPCs/BMSCs (after 7 days of in vitro spin culture) to repair and reconstruct critical-sized mandible defect in rabbit showed that all scaffolds were successfully accurately implanted into the defect area. As revealed by macroscopically and CT at the end of 9 months, defects in the AP40mod/EPCs/BMSCs group were nearly completely covered by normal bone and the degradation rate was 29.9% compared to 20.1% in the AP40mod group by the 3D reconstruction. As revealed by HE and Masson staining analyses, newly formed blood vessels, bone marrow and collagen maturity were significantly increased in the AP40mod/EPCs/BMSCs group compared to those in the AP40mod group. We directly inoculated cells on the novel material to screen for the best inoculation ratio. It is concluded that the AP40mod combination of EPCs/BMSCs is a promising approach for repairing and reconstructing large load bearing bone defect.